PSEUDOANEURISMA ARTERI ILEOKOLIKA SEBAGAI KOMPLIKASI TRAUMA ABDOMEN TUMPUL: LAPORAN KASUS LANGKA - Bastha, Sultan Mahathir; Wintoko, Risal (Medula, 2025)
Mesenteric artery pseudoaneurysm is a rare condition that can occur due to blunt abdominal trauma or postoperative complications. This lesion is often difficult to recognize early due to nonspecific symptoms, leading to diagnosis typically being made through imaging or intraoperative findings. Delayed management can result in serious complications, including bleeding and bowel necrosis. A 59-year-old female patient was reported to have arrived at the Emergency Department of Abdul Moeloeki Hospital with complaints of central abdominal pain for the past week, accompanied by nausea and vomiting. History of abdominal trauma was obtained from a fall in the bathroom one week prior, as well as a traffic accident one year ago. Physical examination revealed abdominal tenderness with muscle rigidity, decreased bowel sounds, and vital signs indicating tachycardia. Laboratory tests were within normal limits. Abdominal ultrasound showed a paraaortic cystic lesion. The patient then underwent exploratory laparotomy, where a pseudoaneurysm of the ileocolic artery was found along with necrosis of the ileum and cecum. A right hemicolectomy was performed. Histopathological examination of the tissue supported the diagnosis of pseudoaneurysm with necrosis. The patient successfully underwent the right hemicolectomy procedure without major postoperative complications. The clinical condition of the patient improved with stable postoperative recovery. Pseudoaneurysm of the ileocolic artery is a rare complication of blunt abdominal trauma that can lead to intestinal necrosis. Early diagnosis requires a high clinical suspicion and confirmation through imaging. Exploratory laparotomy with right hemicolectomy is the definitive therapy for cases with intestinal necrosis.